Domestic Work and the Gig Economy in South Africa: Old wine in new bottles? - Hunt, Abigail; Samman, Emma (Anti-Trafficking Review, 2020)
Based on innovative, mixed-methods research, this article examines the entry of on-demand platform models into the domestic work sector in South Africa. This sector has long been characterised by high levels of informality, precarity, and exploitation, though recent regulatory advances have provided labour and social protections to some domestic workers. We locate the rise of the on-demand economy within the longer-term trajectory of domestic work in South Africa, identifying the ‘traditional’ sector as a key site of undervalued labour. On-demand domestic work platforms create much-needed economic opportunities in a context of pervasive un(der)-employment, opportunities that come with some incremental improvements over traditional working arrangements. Yet we contend that platform models maintain the patterns of everyday abuse found elsewhere in the domestic work sector. These models are premised on an ability to navigate regulatory contexts to provide clients with readily available, flexible labour without longer-term commitment, therefore sidestepping employer obligations to provide labour rights and protections. As a result, on-demand companies reinforce the undervalued and largely unprotected labour of marginalised women domestic workers.